O problema é a cor: discriminação racial na escola - Prezoto, Shirlene de Araujo (2007)
This work presents a reflection about the ethnic-cultural/racial relations in the primary school environment, and has as its objective to highlight the importance and the necessity of a social deconstruction of prejudices and racial discrimination, which are attributed to the black population. It shows through Brazilian history, from its colonization to current times, the ideologies on which the relationship between blacks and whites was constructed, with great disadvantages for the first, especially, in their quest for education and social ascension. It is concluded that prejudice and racial discrimination in schools are presented in a subtle and disguised way, for in Brazilian minds, the racial relationship is cordial. The existence of prejudice and discrimination is denied, even though studies show significant malicious rates for the Brazilian black population, verifying the so called “Brazilian knack” of discrimination, also known as “racism Brazilian style”. Finally, it seeks to evoke the debate about the negative social representations imposed on the black population through stigmas and stereotypes, approaching particularly the issue of ethic-racial education in schools, under Federal Law number 10.639/2003, which establishes imperativeness in teaching Afro- Brazilian History and Culture from elementary to high school level within government and private establishments.